SERAC1 deficiency causes complicated HSP: evidence from a novel splice mutation in a large family - Röben, Benjamin; Langhans, Claus-Dieter (Neurogenetics, 2018)
Objective To demonstrate that mutations in the phosphatidylglycerol remodelling enzyme SERAC1 can cause juvenile-onset complicated hereditary spastic paraplegia (cHSP) clusters, thus adding SERAC1 to the increasing number of complex lipid cHSP genes. Methods Combined genomic and functional validation studies (whole-exome sequencing, mRNA, cDNA and protein), biomarker investigations (3-methyl-glutaconic acid, filipin staining and phosphatidylglycerols PG34:1/PG36:1), and clinical and imaging phenotyping were performed in six affected subjects from two different branches of a large consanguineous family.
Published online first: 15 September 2017
Gesehen am 14.04.2020